VENVS VICTRIX na monetach Julii Mamei – kilka uwag o kreowaniu pamięci historycznej przez ostatnich Sewerów - Smyk, Anita; Maksymiuk, Katarzyna (In Gremium. Studies in History, Culture and Politics, 2025)
The purpose of this research is to attempt to reconstruct Julia Mamaea’s self-presentation and the role that coin issues containing representations of VENVS VICTRIX played in its creation. The importance that Severus Alexander’s Persian campaign played in Julia Mamaea’s self-presentation was also analyzed. Severus Alexander’s hold on power depended heavily on the support of the army, and this was reflected in the coin issues. One of the elements of Julia Mamaea’s self-presentation was her son’s Imitatio Alexandri.